1999
DOI: 10.1046/j.1365-263x.1999.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in tooth maturation patterns in non‐French Canadian boys

Abstract: The shift from below median to above median value was considered an important factor in treatment planning. The data indicate that there is considerable risk for treatment planning prior to the age of 8 years. The risk is highest when the children are less than 6 years of age due to growth prediction uncertainties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
8
1
2
Order By: Relevance
“…Hormonal changes may induce the changes in tooth formation and eruption rates at puberty [9]. However, strong supporting evidence for this hypothesis has not been generated [5,26,30]. Our results conflict with other studies [2,3], which show that dental maturation tends to advance more rapidly in boys than girls.…”
Section: Intra-decade Comparisoncontrasting
confidence: 99%
See 2 more Smart Citations
“…Hormonal changes may induce the changes in tooth formation and eruption rates at puberty [9]. However, strong supporting evidence for this hypothesis has not been generated [5,26,30]. Our results conflict with other studies [2,3], which show that dental maturation tends to advance more rapidly in boys than girls.…”
Section: Intra-decade Comparisoncontrasting
confidence: 99%
“…However, dental maturation patterns of children at similar ages in different ethnic groups may differ, which may affect the dental age estimate accuracy [2][3][4][5][6][7]. Populations in specific geographic regions may exhibit biological differences due to different gene pools, differences in living conditions, climate, socioeconomic status, nutrition and secular changes, which scholars claim are important explanatory factors for the population differences in dental development timing [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagherpour et al (3) reported a greater difference between the chronological and dental age in the age range of 6 -9 years. Similarly, in our study, the maximum difference between the chronological and dental age in both males and females was in the age range of 6 -6.99 years, which is justified by the unpredictable growth pattern at younger ages (22).…”
Section: Discussionsupporting
confidence: 77%
“…The widespread use of this method as an infant age assessment procedure has meant that the results of the Demirjian study have been tested in other populations. Numerous studies over recent decades show a slight delay in maturation of the original French-Canadian population, causing overestimation when the original results of the method are applied to other populations (Bolaños et al, 2003;Davis & Hagg, 1994;Eid et al, 2002;Frucht et al, 2000;Koshy & Tandom, 1998;Liversigde etl., 1999;Loevy & Goldberg, 1999;MacKenna et al, 2002;Nykanen et al, 1998;Nystro et al, 1986;Prabhakar et al, 2002;Staaf et al, 1991;Willems et al, 2001). The aforesaid overestimation varies between some months and several years in age, and it is recommended that standard values based on studies of the same population to which the method is applied are used.…”
Section: Dental Maturationmentioning
confidence: 99%